2014
DOI: 10.1021/jp506323r
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Mg2Si Thin Films by Computational Approaches

Abstract: The semiclassical Boltzmann approach coupled with density functional theory calculations has been used to investigate the structural, electronic, and thermoelectric properties of Mg2Si thin films with 001, 111, and 110 orientations. The most stable slab is found to be that with the 110 orientation. The electronic band gap vanishes for the 001 and 111 thin films whereas for the 110 orientation the film is semiconducting with a band gap ranging from 0.27 to 0.36 eV depending on the number of atomic planes used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Using these data, and the values 100 μV/K, 150 μV/K and 200 μV/K for S at 350 K, 600 K and 900 K, respectively (see Fig. 7), we obtain for ZT around 0.02 at 350 K, 0.07 at 600 K and 0.2 at 900 K. These values, when compared to those calculated for the monocrystalline thin film [16], are about one order of magnitude smaller. The degradation of ZT for the present thin film is probably caused by the disorder observed in the structure.…”
Section: Power Factormentioning
confidence: 63%
See 2 more Smart Citations
“…Using these data, and the values 100 μV/K, 150 μV/K and 200 μV/K for S at 350 K, 600 K and 900 K, respectively (see Fig. 7), we obtain for ZT around 0.02 at 350 K, 0.07 at 600 K and 0.2 at 900 K. These values, when compared to those calculated for the monocrystalline thin film [16], are about one order of magnitude smaller. The degradation of ZT for the present thin film is probably caused by the disorder observed in the structure.…”
Section: Power Factormentioning
confidence: 63%
“…In a previous work [16] we have estimated the relaxation time of electrons in Mg 2 Si thin films from experimental data of the electrical conductivity. The corresponding value was τ ¼ 5 Â 10 À 16 s, which we use hereafter.…”
Section: Power Factormentioning
confidence: 99%
See 1 more Smart Citation
“…This approximation assumed that the scattering time determining the electrical conductivity would not vary strongly with energy on the scale of kT. This method has been widely used to calculate transport properties of thermoelectric materials [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, the grain growth and restructuring into thermodynamically stable structures occur with increasing Ts. Balout et al 22) have recently reported a theoretical result that the surface energy of the (110) surface of Mg 2 Si is the lowest among the (100), (110), and (111) surfaces by performing first-principles calculations based on density functional theory. Therefore, it is considered that the degree of orientation along the (220) plane increases with increasing Ts.…”
Section: Methodsmentioning
confidence: 99%